Legal Analysis of the BPJS Kesehatan Memorandum of Agreement and the Protection of Emergency Patients' Rights - Willy Johan; Nanik Sutarni; Tegar Harbriyana Putra (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
Emergency care is a fundamental health service that must be provided immediately without administrative or financial delays to protect the rights to health and life. However, within the implementation of Indonesia's National Health Insurance (Jaminan Kesehatan Nasional, JKN), the BPJS Kesehatan Memorandum of Agreement (Berita Acara Kesepakatan, BAK), which serves as a guideline for claims settlement, may influence the delivery of emergency care. This study aims to analyze the legal implications of the BAK for the provision of emergency care under Indonesian positive law and to examine it from the perspective of Islamic law. This study employed normative legal research using statutory and case approaches. Legal materials were collected through library research and analyzed using a prescriptive legal approach based on grammatical, systematic, and teleological interpretation, complemented by an analysis grounded in the principles of maqāṣid al-sharī'ah. The findings indicate that several provisions of the BAK, particularly those concerning Death on Arrival (DOA) claims and internal consultations, have the potential to shift the nature of the therapeutic obligation from inspanningverbintenis (obligation of best efforts) to resultaatsverbintenis (obligation of results), creating disharmony with the legal framework governing emergency care and undermining the principle of balance in the legal relationship between BPJS Kesehatan and hospitals. From the perspective of Islamic law, these restrictions are inconsistent with the principles of ḥifẓ al-nafs (protection of life), maṣlaḥah (public interest), and lā ḍarar wa lā ḍirār (no harm and no reciprocating harm), all of which recognize the protection of human life as a primary objective of Islamic law. Therefore, harmonization of BPJS Kesehatan's administrative policies with Indonesia's health law framework is necessary to ensure legal certainty, justice, and optimal protection of patient safety.